ANALYSIS OF STUDENTS PROBLEMS IN TRANSLATING ENGLISH INTO INDONESIAN PROVERBS: AT XI TH GRADE AT SMA MUHAMMADIYAH MATARAM IN ACADEMIC YEAR 2014-2015 - Rima Rahmaniah; Rini Anggriani (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2016)
The purpose of this study is to know the students problemsin translating English into Indonesian proverbs. The writer took the population consist 1 teacher and taken theentire sample that consist of 13 students. The research method applied was a qualitative method by translating proverbs text which is consist 20 items. The result shows that there were eight kinds of problems on  the translation of English proverb into Indonesian, they are (1) the meaning error on using article, (2)  plural, (3) participle, (4) modal auxiliary, (5) demonstrative, (6) gerund, (7) adjective, and (8) comparative degree. This also describe that the students of SMA Muhammadiyah Mataram still have difficulties in translating skill. The students made the grammatical errors in translating English proverb because they have different point of view from the researcher, they are overloaded with many different tasks, they do not think that grammar point is important, the point is more difficult for them than it seems, and they do not know the function of certain grammar.